2021
DOI: 10.47405/mjssh.v6i10.1123
|View full text |Cite
|
Sign up to set email alerts
|

Tinjauan Terhadap Tahap Tekanan Pelajar Universiti Semasa Pandemik COVID-19

Abstract: Pandemik Coronavirus Disease 2019 (COVID-19) yang melanda Malaysia dan seluruh dunia telah memberikan pelbagai implikasi yang sangat besar terutamanya dalam aspek kesihatan mental. Golongan pelajar merupakan golongan yang berisiko mengalami tekanan akibat norma baharu yang wujud susulan pandemik ini. Justeru, kajian ini bertujuan untuk mengenal pasti tahap tekanan pelajar dan mengenal pasti pengaruh jantina dalam menentukan tahap tekanan pelajar. Kajian ini adalah kajian kuantitatif yang menggunakan reka bentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Some studies have examined the stress levels among local university students who had to adapt to some new Teaching and Learning system norms during Malaysia's Movement Control Order (MCO). example is a study by (Aziz et al, 2021) entitled A Survey of the Stress Level of University Students During the COVID-19 Pandemic. They found that out of 400 university students who were their respondents, the majority of university students had a moderate level of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the stress levels among local university students who had to adapt to some new Teaching and Learning system norms during Malaysia's Movement Control Order (MCO). example is a study by (Aziz et al, 2021) entitled A Survey of the Stress Level of University Students During the COVID-19 Pandemic. They found that out of 400 university students who were their respondents, the majority of university students had a moderate level of stress.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is in line with a study conducted to find out the challenges of implementing online learning that affects mental health among HEI students during the COVID-19 pandemic. Along with a previous study (Abdul Aziz et al, 2021), the implementation of this new concept of online learning not only changes the paradigm of how students and lecturers interact, as well as new practices in students' daily routines during online studies, but it also leads to changes in their emotions and behaviours that pose a risk, such as stress, depression, anxiety, and so on. Therefore, students play a critical role in effectively managing issues or pressures with the necessary coping mechanisms in order to combat the COVID-19 wave, which has yet to reach its endpoint.…”
Section: Introductionmentioning
confidence: 90%
“…According to the Ministry of Health Malaysia (2021), the rise of COVID-19 cases across the country has a wide range of consequences, including political, economic, and educational problems, as well as mental health issues (Rashid Abdul Aziz et al, 2021). In an effort to eradicate the spread of this epidemic, the authorities have decided to implement the Movement Control Order (MCO) which was implemented on 18 March 2020, causing people's life patterns and norms to change.…”
Section: Introductionmentioning
confidence: 99%